Insights into catalytic activation of peroxymonosulfate for carbamazepine degradation by MnO2 nanoparticles in-situ anchored titanate nanotubes: Mechanism, ecotoxicity and DFT study - Pan, Fei; Ji, Haodong; Du, Penghui; Taobo Huang; Chong Wang; Liu, Wen (Journal of Hazardous Materials, 2021)
Developing efficient pharmaceuticals and personal care products (PPCPs) degradation technologies is of scientifical and practical importance to restrain their discharge into natural water environment. This study fabricated and applied a composite material of amorphous MnO2 nanoparticles in-situ anchored titanate nanotubes (AMnTi) to activate peroxymonosulfate (PMS) for efficient degradation and mineralization of carbamazepine (CBZ). The degradation pathway and toxicity evolution of CBZ during elimination were deeply evaluated through produced intermediates identification and theoretical calculations. AMnTi with a composition of (0.3MnO2)•(Na1.22H0.78Ti3O7) offered high activation efficiency of PMS, which exhibited 21- and 3-times degradation rate of CBZ compared with the pristine TNTs and MnO2, respectively. The high catalytic activity can be attributed to its unique structure, leading to a lattice shrinkage and small pores to confine the PMS molecule onto the interface. Therefore, efficient charge transfer and catalytic activation through MnOTi linkage occurred, and a MnTi cycle mediating catalytic PMS activation was found. Both hydroxyl and sulfate radicals played key roles in CBZ degradation. Theoretical calculations, i.e., density functional theory (DFT) and computational toxicity calculations, combined with intermediates identification revealed that CBZ degradation pathway was hydroxyl addition and NC cleavage. CBZ degradation in this system was also a toxicity-attenuation process.
Keywords: Carbamazepine; DFT; MnO; Peroxymonosulfate; Titanate nanotubes